Application and Effect of the Gymnastic Exercise Mode during Chemotherapy for Breast Cancer Patients - Feifei Xie (Journal of Chemistry)
Breast cancer is one of the most common malignant tumors in women, which seriously threatens the health of women. With the improvement of living standards, the incidence rate of breast cancer is also rising. In the past ten years, the incidence rate of breast cancer in China’s major cities has increased by 37%, far higher than that in Europe and America. At present, chemotherapy and radiotherapy are the main treatment methods for breast cancer, but many patients will have cancer-related fatigue after surgery. Some studies believe that appropriate sports can improve cancer-related fatigue, but there is no specific research in this area. In view of this problem, this paper puts forward a rehabilitation training method based on gymnastics for breast cancer surgery. This paper is divided into three parts. The first part is the basic theory and core concept of breast cancer and cancer-related fatigue. Through the in-depth study of the theory, this paper believes that breast cancer patients paying attention to rehabilitation training can effectively improve cancer-related fatigue and affect the final therapeutic effect. The second part is the rehabilitation training program based on the way of gymnastics. The corresponding experimental model is established by using real cases as samples. In order to ensure the quality of the experiment, this paper gives the treatment plan in detail and establishes a unified evaluation system. In the third part of this paper, the relevant experiments and results analysis are given, and through data analysis, this paper believes that gymnastics can effectively help breast cancer patients with postoperative rehabilitation and continuous recovery of the upper limb function and improve cancer-related fatigue and other issues.